1979
DOI: 10.1128/jb.137.2.846-853.1979
|View full text |Cite
|
Sign up to set email alerts
|

Acetohydroxy acid synthase I of Escherichia coli: purification and properties

Abstract: Several properties of the three acetohydroxy acid synthases of Escherichia coli have been compared in crude extracts. The three enzymes can be readily distinguished from each other. Acetohydroxy acid synthase I, the product of the iluB gene, has been purified to near homogeneity. The purification was made possible by the fact that the enzyme was maintained in buffers of a high ionic strength or in buffers containing glycerol. Density gradient centrifugation studies indicated that the enzyme exists as a dimer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…This value is comparable to those found in other acetolactate forming systems (GRIMMINGER andUMBARGER 1979, SCHLOSS el ul. 1985).…”
Section: Msupporting
confidence: 87%
“…This value is comparable to those found in other acetolactate forming systems (GRIMMINGER andUMBARGER 1979, SCHLOSS el ul. 1985).…”
Section: Msupporting
confidence: 87%
“…2). The 57and 58-kDa polypeptides of AHAS from wheat were similar in size to the single subunit of AHAS isolated from barley (Dumer and Boger 1988) and to the large subunit of AHAS from bacteria (Grimminger and Umbarger 1979, Eoyang and Silverman 1984, Schloss et al 1985. In contrast, a single polypeptide of molecular mass of approximately 65 kDa has been identified in immunoblots of crude extracts from a wide range of plant tissues using monoclonal antibodies raised against synthetic peptides as immunogen, or polyclonal antibodies raised agairtst an Arabidopsis AHAS fusion protein expressed in E. coli (Singh et al 1991a,b).…”
Section: Discussionsupporting
confidence: 53%
“…1988a). Most reports of the native molecular mass of AHAS from bacteria fall in the range between 130 and 160 kDa (Grimminger and Umbarger 1979, Eoyang and Silverman 1984, Schloss et al 1985, Alexander-Caudle et al 1990), although 68-, 140-and 500-kDa forms of the enzyme were reported in Neurospora crassa (Tanaka and Kuwana 1984).…”
Section: Discussionmentioning
confidence: 99%
“…AHAS expression and purification from native sources has been described in detail previously by Duggleby et al [1]. Enterobacterial isozymes are more easily purified from native sources than eukaryotic AHASs [34][35][36]. The respective expression of the three isozymes is regulated in different ways in enterobacteria.…”
Section: Purification and Characterizationmentioning
confidence: 99%